2023
DOI: 10.7717/peerj.15039
|View full text |Cite
|
Sign up to set email alerts
|

Depression and insomnia among healthcare professionals during COVID-19 pandemic in Ethiopia: a systematic review and meta-analysis

Abstract: Introduction Healthcare professionals play a great role in the struggle against COVID-19. They are highly susceptible to COVID-19 due to their responsibilities. This susceptibility directly affects their mental health status. Comprehensive evidence on prevalence of depression and insomnia during this pandemic is vital. Thus, this study aims to provide the pooled prevalence of depression and insomnia, and their associated factors during the COVID-19 pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…Our results found that there is a significant relationship between insomnia and the family situation of HWCs at the first time point, with higher means for HCWs who had a partner. This is in accordance with previous research during the COVID-19 pandemic that reported a direct association between being married and depression or insomnia [ 49 ]. It should be noted that the first time point in our study was during the confinement phase of the pandemic, and during this period, findings were found linking cohabitation with a partner with anxiety [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results found that there is a significant relationship between insomnia and the family situation of HWCs at the first time point, with higher means for HCWs who had a partner. This is in accordance with previous research during the COVID-19 pandemic that reported a direct association between being married and depression or insomnia [ 49 ]. It should be noted that the first time point in our study was during the confinement phase of the pandemic, and during this period, findings were found linking cohabitation with a partner with anxiety [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the study showed that marital status is a significantly associated factor with depression, which is supported by the studies conducted in Dessie Comprehensive Specialized Hospital, Ethiopia [ 14 ], and systematic review conducted in Ethiopia [ 27 ], Egypt [ 32 ], Nigeria [ 35 ], Saudi Arabia [ 28 ], and Baghdad [ 31 ]. This might be because every human being in nature needs love and belongingness, so having a soul mate might prevent loneliness, which might worsen the problem.…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, the finding is lower than the finding from a systematic review and meta-analysis conducted in Ethiopia, which was 40% [ 27 ]. The discrepancy between a systematic review and meta-analysis conducted in Ethiopia might be due to studies conducted during the COVID-19 pandemic, which might increase the problem as there was a lower understanding of COVID-19 at the beginning.…”
Section: Discussionmentioning
confidence: 64%
“…The findings of the study showed that marital status is a significantly associated factor with depression, which is supported by the studies conducted in Dessie Comprehensive Specialized Hospital, Ethiopia [14], and systematic review conducted in Ethiopia [27], Egypt [32], Nigeria [35], Saudi Arabia [28], and Baghdad [31]. This might be because every human being in nature needs love and belongingness, so having a soul mate might prevent loneliness, which might worsen the problem.…”
Section: Plos Onementioning
confidence: 52%